Design and validation of a multimodal low-budget Raman-microscope for liquid and solid phase applications - Will, Stefan; Koch, Hanna; Noack, Kristina (Optical Methods for Inspection, Characterization, and Imaging of Biomaterials II, 2015)
Confocal Raman microscopy is a powerful tool to measure small sample volumes or solids. Since commercial Raman microscopes are expensive and a change of the laser wavelength or the excitation path is hardly possible after the installation, we constructed a multimodal low-budget Raman microscope. Thus, it was possible to significantly increase the flexibility in terms of excitation wavelengths, paths, and planes. Furthermore, the asset costs were reduced by a factor of 1.7. By using commercial as well as home-built objectives to adapt the working distance and the magnification to the system under investigation, the self-constructed Raman microscope offers the possibility to measure big sample volumes, too. The obtained Raman spectra were validated by Raman spectra from a commercial Raman microscope. With a comparable measurement setting it was possible to increase the signal intensities, but with a slightly lower SNR. However, based on the great flexibility of the set-up, e.g., the laser power or the excitation wavelength can be adapted to increase the SNR. Furthermore, measurement times can be decreased. With this low-budget self-constructed Raman microscope high quality Raman microscopy and micro spectroscopy can be performed with a high flexibility to fast adapt the set-up to the sample under investigation which is not offered by commercial microscope
Keywords: Raman microscope; low-budget; confocal; validation; multimodal; application-oriented